Contabilidade gerencial: uma metodologia para implantação nas pequenas empresas - Viana, Tatiana Leitão (2007)
In the social economic context, filled with transformations, where uncertainty and unpredictability about the future are predominant, the use of management information accounting has vital importance, being fundamental to the survival or growth of companies in general. In order to be updated ad successful, business need to promote their organizational development. Considering the particularities of small business and their increasing contribution to the country’s economy, this study aims at proposing a methodology of management accounting inclusion in small business in order to facilitate their process of management. Our specific objectives are: identifying and analyzing if the pieces of information received contribute to the referred process; verifying if such pieces of information respond to the inherent characteristics demanded by the organizational unit that create norms in terms of utility; identifying which are their information necessities; defining strategies for the generation of information from the elaboration of management reports. For the execution of these objectives, 50 (fifty) small business were interviewed in Fortaleza (CE). We developed a documental, bibliographic and field work research, in a qualitative and quantitative approach and of exploratory-descriptive nature. From the results obtained it was verified that for 90% of them the pieces of information don’t respond to their inherent characteristics because they’re not opportune, reliable, relevant, comprehensive and useful. As to the information necessities, it was identified that 80% lack information about their social-financial performance, especially: inventory control; control and management of costs; information about selling price; ad basic financial analysis. Thus, based on the catalogued opinions we concluded that management accountability must be inserted in the decisive process of small business in order to improve them and provide a competitive differential. This way, in order to hopefully fulfill the gap we present a methodology to incorporate several tools related to management account, considering five steps, each one comprehending a set of tasks aiming at supporting the decisive process of small business adding values as well as providing a competitive differential.